Endoscopic treatment of vesicoureteral reflux in children with subureteral dextranomer/hyaluronic acid injection: a single-centre, 7-year experience - Biočíc, Mihovil (Canadian Medical Association, 2012)
BACKGROUND: The goals of medical intervention in patients with vesicoureteral reflux are to allow normal renal growth, prevent infections and pyelonephritis, and prevent renal failure. We present our experience with endoscopic treatment of vesicoureteral reflux in children by subureteral dextranomer/hyaluronic acid copolymer injection. METHODS: Under cystoscopic guidance, dextranomer/hyaluronic acid copolymer underneath the intravesical portion of the ureter in a subureteral or submucosal location was injected in patients undergoing endoscopic correction of vesicoureteral reflux. RESULTS: A total of 282 patients (120 boys and 162 girls) underwent the procedure. There were 396 refluxed ureters altogether. The mean age of patients was 4.9 years. The mean overall follow-up period was 44 months. Among the 396 ureters treated, 76% were cured with a single injection. A second and third injection raised the cure rate to 93% and 94%, respectively. Twenty-two (6%) ureters failed all 3 injections, and were converted to open surgery. CONCLUSION: Endoscopic treatment of vesicoureteral reflux can be recommended as a first-line therapy for most cases of vesicoureteral reflux, because of the short hospital stay, absence of complications and the high success rate.